Deposit Insurance, Remittances, and Dollarization : Survey-Based Evidence from a Top Remittance-Receiving Country - Grigorian, David (IMF Working Papers; Working Paper ;, 2017)
The paper uses a unique survey of remittance-receiving individuals from Tajikistan to study the impact of policy awareness on consumer behavior. The results show that knowledge of deposit insurance encourages the use of formal channels for transmitting remittances and reduces dollarization. Given the size and importance of remittances in Tajikistan, improving financial literacy and better publicizing details of the social safety net may encourage a more frequent use of formal channels for transferring remittances and reduce reliance on foreign exchange for transaction purposes. This is likely to improve bank profitability, enhance financial stability, and improve access to finance.